Butterfly community structure in a rehabilitated post-mining tropical rainforest landscape, Sorowako, South Sulawesi, Indonesia - SITTI NURAENI; ANDI PRASTIYO; SITI HALIMAH LAREKENG; ANDRI ARDIANSYAH; ALDI ALDI; SRI WAHYUNI JUFRI (Society for Indonesian Biodiversity, 2025)
Abstract. Nuraeni S, Prastiyo A, Larekeng SH, Ardiansyah A, Aldi, Jufri SW. 2025. Butterfly community structure in a rehabilitated post-mining tropical rainforest landscape, Sorowako, South Sulawesi, Indonesia. Biodiversitas 26: 4761-4774. Human disturbances, such as mining, can disrupt butterfly communities, which serve as important ecological indicators. This study evaluated butterfly diversity and richness in conservation and non-conservation zones within the mining area of PT Vale, South Sulawesi, Indonesia. Data analysis involved diversity indices, t-tests, and Pearson correlations, with cluster analysis grouping sites and PCA exploring links between butterfly abundance and microclimatic factors. A total of 40 butterfly species belonging to five families, mainly Nymphalidae, Pieridae, and Lycaenidae, were recorded from 18 sampling transects during a four-week field period using standard transect and sweep net methods. The most frequently recorded species was Catopsilia pomona (Pieridae) with a relative abundance of 20.00%, followed by Ideopsis juventa (Nymphalidae) with 19.80%. Results showed that non-conservation sites had slightly higher diversity (1.43±0.67), richness (5.63±4.94), and evenness (0.48±0.13), while dominance was higher in conservation transects (0.52±0.32). This spatial comparison suggests that human-made habitats may support butterfly diversity but also lead to increased species dominance in more intact environments. The t-test showed a significant difference only in evenness. No significant correlations were found between biodiversity indices and environmental variables based on Pearson's analysis. Cluster analysis identified two main site groups: the first included most conservation transects (SC2, SC5, SC6) and some non-conservation transects (SN2, SN3), while the second contained most non-conservation transects and a few conservation sites (SC4, SC8), indicating overlapping habitat features. PCA revealed that light intensity explained 90.15% of the variation in the first principal component, and altitude explained 79.24% in the second, demonstrating their strong influence on butterfly distribution. These results provide baseline data on butterfly community structure and highlight the ecological differences between conservation and disturbed zones.